Triad of agroecological tourism: Resources, supply and demand for sustainable development on the northern coast of Ecuador - Segura-Rodríguez, Ana del Carmen (2025)
Agro-ecological tourism is presented as a driver of sustainable development in rural communities, but its implementation faces the challenge of a lack of alignment between resources, supply, and demand. This problem is particularly evident in La Unión de Atacames, Ecuador, where, despite its rich cultural heritage, there is a lack of comprehensive strategic planning. Therefore, the purpose of this study was to analyze how the interaction of these three components can strengthen this model of tourism. The research used a participatory methodology, divided into three phases: diagnosis, market study, and resource inventory.  Data was collected from 129 key informants using techniques such as interviews and surveys. The findings revealed the presence of significant natural and cultural resources, as well as a clear interest from visitors. However, the study also found that the tourism offers are limited and the infrastructure inadequate. The main conclusion of the analysis is that the success of agro-ecological tourism in this area depends on the strategic alignment of its resources, supply, and demand. Consequently, it is recommended to formalize the infrastructure, diversify tourism products, and ensure strong institutional support to transform the community's potential into an economically viable and sustainable development model.